2006
DOI: 10.1080/14992020600782956
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of bilateral cochlear implants and/or hearing aids in children

Abstract: This study evaluated functional benefits from bilateral stimulation in 20 children ages 4 -14, 10 use two CIs and 10 use one CI and one HA. Localization acuity was measured with the minimum audible angle (MAA). Speech intelligibility was measured in quiet, and in the presence of 2-talker competing speech using the CRISP forced-choice test. Results show that both groups perform similarly when speech reception thresholds are evaluated. However, there appears to be benefit (improved MAA and speech thresholds) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
202
3
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(222 citation statements)
references
References 34 publications
14
202
3
3
Order By: Relevance
“…Further, Galvin and colleagues (Galvin et al 2007) reported that children who received their second CI after 4 years of age did not show any improvement using both implants over unilateral conditions on tests of sound localization after 6-13 months of bilateral experience. Litovsky (Litovsky et al 2006a;Litovsky et al 2006b;Litovsky et al 2004) also report high degrees of variability within groups of implanted children, which could not always be attributed to duration of deafness or length of bilateral implant use. In order to better predict and promote improved outcomes with bilateral cochlear implants, further research is needed to gain understanding into what factors determine localization abilities in these children.…”
Section: Usersmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, Galvin and colleagues (Galvin et al 2007) reported that children who received their second CI after 4 years of age did not show any improvement using both implants over unilateral conditions on tests of sound localization after 6-13 months of bilateral experience. Litovsky (Litovsky et al 2006a;Litovsky et al 2006b;Litovsky et al 2004) also report high degrees of variability within groups of implanted children, which could not always be attributed to duration of deafness or length of bilateral implant use. In order to better predict and promote improved outcomes with bilateral cochlear implants, further research is needed to gain understanding into what factors determine localization abilities in these children.…”
Section: Usersmentioning
confidence: 99%
“…However, it is not currently known whether bilateral cochlear implantation is sufficient to restore the precision of the normal binaural auditory system required to make interaural sound comparisons. Previous research has shown improved sound localization in children with bilateral implants compared to unilateral implant users (Litovsky, 2004;Grieco-Calub et al, 2008;Van Deun, 2009b). Others have shown that adults with two implants can use inter-implant signal level cues to localize sounds, but are less successful at using inter-implant sound timing cues (van Hoesel and Clark, 1997;van Hoesel and Tyler, 2003;van Hoesel, 2004;Litovsky, 2004).…”
Section: Background and Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations